Fear of disease progression among breast cancer patients in China: a meta-analysis of studies using the fear of progression questionnaire short form - He, Jia-Li; Xu, Hui-Qiong; Yang, Jing; Hou, Dong-Jiang; Gong, Xiao-Yan; Lu, Xian-Ying; Wang, Wei; Cai, Ming-Jin; Yu, Yu-Feng; Gao, Jing (Frontiers in Psychology, 2023)
Background: Fear of disease progression (FoP) is among the most prevalent and major psychological burdens breast cancer patients encounter. Excessive FoP may result in serious adverse effects for patients. FoP in breast cancer patients has gained attention recently; however, its prevalence in China is unknown.Objectives: This meta-analysis and systematic review aimed to assess the overall FoP among Chinese breast cancer patients to make recommendations for treatment and care.Methods: Systematic search databases included PubMed, EMbase, The Cohrane Library, Web of Science, CINAHL, PsycINFO and 4 Chinese databases (Wan Fang Data, CBM, VIP and CNKI). The retrieval time ranged from the database's establishment to March 20, 2023. After two researchers independently evaluated the literature, retrieved information, and assessed the risk of bias for the included literature, Stata 15.1 software was used to conduct a meta-analysis.Results: A total of 37 moderate or high-quality studies involving 9,689 breast cancer patients were included. Meta-analysis showed that the pooled mean score of FoP for Chinese breast cancer patients was 33.84 [95% CI (31.91, 35.77)], prediction interval (21.57 46.11). The subgroup study found that FoP levels varied among breast cancer patients of different regions, ages, educational levels, marital statuses, residences, illness stages, and disease statuses.Breast cancer patients have higher FoP scores. Healthcare workers should be concerned. We expect that more relevant research will be undertaken and more effective interventions will be developed. Patients can manage their illness and improve their quality of life by reducing their fears.